2013
DOI: 10.1002/ajmg.a.36274
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing in nonsyndromic intellectual disability: From a negative molecular karyotype to a possible causative mutation detection

Abstract: The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 45 publications
5
31
0
3
Order By: Relevance
“…An X-inactivation pattern of 73:27 was reported. These previously reported female patients seem to be on the extreme ends of the phenotypic spectrum in comparison to our new cases, with one patient being relatively mildly affected,10 while the other two have a phenotype comparable to our most severely affected cases 911 Although we observe a comparable clinical picture in most female cases, this illustrates that the phenotypes of females affected by KIAA 2022 mutations can be very variable.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…An X-inactivation pattern of 73:27 was reported. These previously reported female patients seem to be on the extreme ends of the phenotypic spectrum in comparison to our new cases, with one patient being relatively mildly affected,10 while the other two have a phenotype comparable to our most severely affected cases 911 Although we observe a comparable clinical picture in most female cases, this illustrates that the phenotypes of females affected by KIAA 2022 mutations can be very variable.…”
Section: Discussionsupporting
confidence: 76%
“…The reported phenotype was comparable to the previously described male phenotype, with severe ID, microcephaly, autistic behaviour, growth retardation and facial dysmorphia, without epilepsy. Athanasakis et al 10 reported a 13-year-old girl with mild ID and a de novo non-sense mutation of KIAA2022 (p.Arg628*) as part of a larger study which included patients with ID and absence of dysmorphic features, normal growth parameters and no seizures or malformations. The X-inactivation pattern was 65:35.…”
Section: Discussionmentioning
confidence: 99%
“…The H3K4me3 demethylase KDM5C is mutated in X-linked mental retardation (Iwase et al, 2007;Abidi et al, 2008;Adegbola et al, 2008;Gonçalves et al, 2014). Further, mutations in KDM5B have been reported in individuals with non-syndromic intellectual disability and autism spectrum disorders (Athanasakis et al, 2014;De Rubeis et al, 2014;Iossifov et al, 2014) and mutations in KDM5A have been linked to an autosomal recessive form of intellectual disability (Najmabadi et al, 2011). Similarly, several genes implicated in cytoskeleton dynamics are mutated in intellectual disability and autism spectrum disorders (Nadif Kasri and Van Aelst, 2008;Ba et al, 2013;Hu et al, 2014;Srivastava and Schwartz, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, all variants in KDM5B had been described in cancer. Next-generation sequencing has since revealed a de novo splicing mutation (c.283A>G) in KDM5B in an individual with nonsyndromic ID [19] (Figure 2). Six additional variants were newly identified in exome sequencing of a large cohort of individuals with ASD [3,4].…”
Section: Kdm5b Mutations In Id and Asdmentioning
confidence: 99%
“…Shen et al provided a comprehensive view on writer and eraser enzymes for H3K4me in brain disorders from a clinical perspective, including data from human samples and animal models [17]. More recently, alterations of KMT2F in schizophrenia [2], KDM1A in Kabuki/ KBG syndrome [18], and KDM5A and KDM5B in ID [1,19] have been reported, which were not covered by these earlier reviews. New exome sequencing of a large cohort of individuals with ASD also identified KMT2C and KDM5B [3,4].…”
mentioning
confidence: 99%